The Effect of the “My Parent is My Digital Game Guide” Family Education Program on Children’s Digital Game Addiction and Parental Mediation - Ölmez, Esin; Feyman Gök, Nihan (International Electronic Journal of Elementary Education, 2025)
Playing games has an indispensable place throughout life, especially in childhood. It is known that the tendency to play digital games has increased due to technological developments, increasing urbanization, and decreasing playgrounds. In this context, it is thought that it is important for families to gain awareness in children's digital game preferences and game playing processes. The aim of this study is to examine the effect of the training program prepared for parents with preschool-age children on digital game parental guidance strategies. The study group of the research consists of 200 parents selected from the parents of preschool children in the central district of Ankara province in the 2022-2023 academic year. Parents were determined by convenience sampling technique. Three data collection tools were used as data collection tools for this study: ''Digital Game Addiction Tendency (DOBE)'', ''Digital Game Parental Guidance Strategies Scale (DOERS)'' (Budak, 2020) and ''Personal Information Form''."My Parent is My Digital Game Guide" program was implemented for seven weeks and seven hours in total. The findings obtained from the research, normality and homogeneity tests were performed to test the parametric test assumptions for the mean values of parents with preschool children. In obtaining the findings; Kolmogorov-Smirnov Z test, Homogeneity of Variances test, Mann Whitney U test and Kruskal Wallis H analysis, Wilcoxon signed ranks analysis were performed. According to the results of the study, it was determined that there was a significant difference between before and after the implementation of the family education program. According to the results of the analysis, it was seen that the family education program was effective on parental digital game guidance strategies. In addition, it was seen that the digital game addiction tendencies of boys were more addictive than girls. Parent education programs that include digital game guidance for parents can be expanded.